Optimization Of Round Shape Portable Vacuum Clamping Based On Machining Parameters - Ab Wahab, Norfariza; Mustapha, Mohd Khairulazwan; Nordin, Abd Khahar; Zahari, Madiha; Abd Mutalib, Nurliyana; Mohd Nor, Rozilawati; Md Nasir, Nur Syuhada (Asian Research Publishing Network (ARPN), 2020)
The aim of this project is to optimize the round shape portable vacuum clamping based on machining parameters. The selected machining parameter is spindle speed, depth of cut and feed rate. The vacuum clamping was tested to evaluate and analyse the result of surface roughness and time setting. The result shows that the portable round shape vacuum clamping is the best clamping system compare with conventional vise in term of setup time. The time is taken for setting the workpiece on the clamping device for vacuum clamping is 13.6 seconds which is faster than conventional vise 54.7 seconds. For surface roughness, the smooth surface is 1.627 µm at 910 RPM of spindle speed. 910 RPM spindle speed is most suitable for machining 0.5mm depth of cut on portable round shape vacuum clamping